Analisis Kemandirian Belajar Mata Pelajaran Dasar Listrik dan Elektronika pada Sekolah Menengah Kejuruan - Khair Kauli; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This researcher is in the background because of the problem of the impact of COVID-19 on the world of education. In this study, it aims to reveal how much the percentage influence of learning independence on student learning outcomes. This self-reliance population used a sample taken from students of SMK1 West Sumatra, Department of Electronic Engineering class X and selected randomly (simple, rundown and sampling). Data on student learning outcomes are taken from semester scores in teachers of basic electrical electronics subjects at SMK 1 West Sumatra. Meanwhile, data on learning independence is obtained from questionnaires that are distributed to students using a likert scale that has been validity and reality. From the results of data analysis on the influence of learning independence, it shows that there is a significant relationship between the learning outcomes of grade 10 students in the basic subjects of electronic electricity at SMK 1 West Sumatra. It can be concluded that in this study there is an influence of learning independence on class X Electronics students of SMK 1 West Sumatra on the basic subjects of electronic electricity, after conducting this study, student learning independence is getting higher and student learning outcomes are better.